1q21.1 Duplication Syndrome and Anorectal Malformations: A Literature Review and a New Case - Maria Minelli; Chiara Palka Bayard de Volo; Melissa Alfonsi; Serena Capanna; Elisena Morizio; Maria Enrica Miscia; Gabriele Lisi; Liborio Stuppia; Valentina Gatta (Current Issues in Molecular Biology)
Background: Anorectal malformations (ARMs) are a common pediatric surgical problem with an incidence of 1:1500 to 1:5000 live births. The phenotypical spectrum extends from anal stenosis to imperforate anus with or without anal fistula to persistent cloaca. They can manifest as either non-syndromic or syndromic conditions. Various environmental and genetic risk factors have been elucidated. The widespread use of genetic screening tests for the investigation of developmental disorders increased the recognition of copy number variants (CNVs) of the 1q21.1 region. Duplications have also been associated with a multitude of congenital anomalies, such as heart disease, short stature, scoliosis, urogenital, and ARMs, and they have also been found in healthy individuals. The aim of this manuscript is to contribute to the definition of the phenotype associated with 1q21.1 duplications. Case presentation: The present case describes a male, referred to us for an ARM, in whom array—comparative genomic hybridization (array-CGH) identified 1q21.1 duplication inherited from his healthy mother. No other genetic test was performed on the patient. Conclusions: We propose considering genetic evaluation and analysis in patients with only one congenital malformation in order to eventually make an early diagnosis and a better quality of treatments.